Economic, social, and environmental sustainability in development theory and urban planning practice - A. D. BASIAGO (The Environmentalist 19, 145]161:1999., 1999)
In ten years, more than half the world's population will be living in cities. The United NationsUN.has stated that this will threaten cities with social conflict, environmental degradation and the collapse of basic services. The economic, social, and Environmental planning practices of societies embodying `urban sustainability' have been proposed as antidotes to these negative urban trends. `Urban sustainability' is a doctrine with diverse origins. The author believes that the alternative models of cultural development in Curitiba, Brazil, Kerala, India, and Nayarit, Mexico embody the integration and interlinkage of economic, social, and environmental sustainability. Curitiba has become a more livable city by building an efficient intra-urban bus system, expanding urban green space, and meeting the basic needs of the urban poor. Kerala has attained social harmony by emphasizing equitable resource distribution rather than consumption, by restraining reproduction, and by attacking divisions of race, caste, religion, and gender. Nayarit has sought to balance development with the environment by framing a nature-friendly development plan that protects natural systems from urban development and that involves the public in the development process. A detailed examination of these alternative cultural development models reveals a myriad of possible means by which economic, social, and environmental sustainability might be advanced in practice. The author concludes that while these examples from the developing world cannot be directly translated to cities in the developed world, they do indicate in a general sense the imaginative policies that any society must foster if it is to achieve `urban sustainability